Land Dispute Resolution Due to the Issuance of Double Certificates by the National Land Agency - Harniwati; Engrina Fauzi; Fauzan Zakir; Miasiratni; Uci Asriadi (Ekasakti Journal of Law and Justice, 2026)
Land as one of the human needs has a very important role in the basis of human life. The term agrarian itself in Indonesia refers to Law Number 5 of 1960 concerning Basic Agrarian Regulations, hereinafter known as UUPA. Based on the provisions of Article 1 paragraph (2) of UUPA, it states that the words "earth, water, space and the natural resources contained therein" are national assets. UUPA is a legal umbrella in regulating earth, water, space and other natural resources. Based on Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, which states that control of earth, water and the natural resources contained therein is handed over to the Republic of Indonesia to be used as appropriate to create the prosperity of the people. Land issues have a long journey. Various land disputes and conflicts due to frequent conflicts over power struggles over control of land rights, thus encouraging the government as the holder of the highest authority to be required to provide a mechanism for resolving land disputes and conflicts involving the National Land Agency. A land dispute is a specific dispute concerning rights or interests where the parties file claims, counterclaims, and terminate those claims. The granting and determination of land rights is the duty and authority of the National Land Agency, with procedures stipulated in laws and regulations based on Presidential Regulation Number 63 of 2013 concerning the National Land Agency (BPN). One of the duties of the National Land Agency is to issue land certificates. Certificates, as evidence that the land has been registered by an authorized government agency, are strong and authentic evidence. However, in practice, the issuance of duplicate certificates is a serious problem that threatens legal certainty and justice for the community. Duplicate certificates occur when two or more certificates are issued for the same plot of land, often caused by administrative errors, data manipulation, or acts of corruption in the land registration process. In conducting this research, the author used a juridical-normative approach. This approach aims to conduct research based on relevant legal provisions, records, and other available media. The data collection technique used was secondary data literature study as the main research basis.